THE INFORMATION STRUCTURE IN ARABIC-JAVANESE TRANSLATION: CASE STUDY IN THE BOOK OF BIDAYAH AL-HIDAYAH - Muhammad Yunus Anis; Eva Farhah; Afnan Arummi (LPPM IAIN Kudus, 2017)
Communication involves the actual use of language in real. As we have known that language is the main medium for communication. One of the important thing to develop the effective communication is by packaging the structure of information. There are two basic elements in the information, they are: theme and rheme. Theme had been considered as the known information and the rheme absolutely had been considered as new information. This paradigm based on the Systemic Functional Linguistics (SFL). Halliday considers language as having three main functions: (1) the ideational function; (2) the interpersonal function; and (3) the textual function. This paper will focus in the textual function and “clause as a message”. Arabic language has a unique structure of clauses, we can find two basic notions (mubtada’+khabar) and (fi’l+fa’il), in the other hand, semantically, we can find (musnad+musnad ilaih), so this article tried to find the correlation between the structure of Arabic clauses with (theme+rheme) construction. This article also will find out the kinds of theme in Arabic language (multiple themes, clause as themes, and predicated themes). Theme as an initial element in SFL should be described by looking the rheme in the text. The method in this research was divided into three parts: (1) collecting the data from the book of Modern Written Arabic and also some articles in the Arabic-Javanese translation book Bidayah al-Hidayah, the data is the clauses with nominal and verbal initial; (2) analysis data, using the descriptive analysis and distributional method; and (3) reporting the data (formal and informal). The result of this article had concluded that there is a near connection between (mubtada’+khabar), (fi’l+fa’il), and (musnad+musnad ilaih) with the theme and rheme construction based on the SFL theory.